Reforming the international monetary system in the 1970s and 2000s: Would a special drawing right substitution account have worked? - McCauley, R; Schenk, C (Wiley, 2015)
Advocates of a more pluralistic international monetary and financial system seek to reduce reliance on a single national currency and to bring international liquidity under collective control. One recently revived proposal would transform US dollar official reserves into claims denominated in the IMF's key currency basket, Special Drawing Rights (SDRs). Drawing on new archival evidence and simulations, this article highlights issues that derailed earlier agreement on such an account and shortcomings of design and ambition revealed by subsequent developments. One design issue was account losses if US dollar yields failed to exceed SDR yields enough to offset dollar depreciation. In fact, uncovered interest parity did not hold and could well have left the account persistently insolvent. Another shortcoming was ambition: the proposed account proved simply too small to achieve the desired lowering of the dollar's share of foreign exchange reserves. Any new proposal needs to address these shortcomings.